Female violence in terror attacks: a phenomenological analysis based on evidence from the "Intifada of the Individuals" - Ben-Shalom, Uzi (Crime, law and social change, 2023)
This research focuses on violence by females who were involved in terror attacks in Israel during the Intifada of the Individuals between September 2015 and October 2016. Videos of encounters during this conflict present a sample of females perpetrating terror attacks, responding as armed security personnel, or participating (or not) in mob violence following the attack. Using the Three Agent Model of terror attacks, we sorted female modes of participation into "Aggressor," "Disruptor," and part of "Crowd." We analyzed 20 terror attacks with female aggressors and 8 terror attacks with female disruptors, extrapolating the information from analysis of the videos, open-source materials on the Internet, and in-depth interviews. Attacks by female aggressors usually involved numerous "Threat Moves" and were generally disorganized; nevertheless, these aggressors were likely to be killed. Female disruptors were predominantly in uniform and armed. They conveyed a viewpoint of being equal in operational prowess to their fellow soldiers who were male. Some of them expressed an intention to moderate the level of violence during friction, but the video analysis revealed that, like their male fellows, they were likely to inflict lethal violence or to risk being killed. We were not able to locate any evidence of involvement of females in crowd violence following terror attacks, nor that crowd violence by males directed towards subdued female aggressors. We contend that the level of institutional preparation is the most likely explanation for these patterns of aggression on both sides of the political conflict, for women terrorists and women combatants alike. We discuss the utility and limitations of our theoretical and empirical approaches to understanding female aggression.